Information System Development for Dental Clinic Using ReactJS and Prisma ORM - Farrel Farhan; Nur Cahyo Wibowo; Rizka Hadiwiyanti (Komunitas Dosen Indonesia, 2025)
drg. Irna Dental Clinic is a healthcare facility that still uses a semi-manual system for patient registration and medical recordkeeping, leading to various issues such as service delays, recording errors, and difficulties in managing patient data. This study aims to design and develop a web-based information system that integrates administrative processes, including patient registration, appointment scheduling, medical record management, and online consultation features. The system was developed using the Software Development Life Cycle (SDLC) Waterfall model, employing modern web technologies for the frontend, user interface design, and database management. System testing was conducted using the Black Box Testing method with 48 test cases, all of which were successfully executed as expected. This indicates that all the core features of the system function properly and consistently. The results show that the system can improve the clinic’s operational efficiency, simplify access to information, and support more organized and modern patient services. By transitioning from a semi-manual system to a fully digital one, the clinic can provide faster, more accurate, and easily accessible services, significantly enhancing the overall patient experience and helping the clinic keep up with technological advancements in healthcare service delivery. Additionally, the feedback from the clinic's staff (doctors and admins) confirmed that the system meets the operational goals and provides a more efficient solution compared to the previous manual processes.